Evolution and control of H5N1: A better understanding of the evolution and diversity of H5N1 flu virus and its host species in endemic areas could inform more efficient vaccination and control strategies. (11th January 2013) - Watanabe, Yohei; Ibrahim, Madiha S; Ikuta, Kazuyoshi
Abstract : The evolutionary dynamics of the H5N1 virus present a challenge for conventional control measures. Efforts must consider the regional aspects of endemic H5N1.